Професійне самовизначення старшокласників: поняття, фактори впливу - Гунчак, Олександр,Тетяна Равлюк (My University, 2024)
The actual problem of professional self-determination of high school students has been raised. The essence of the concept of "professional self-determination of personality " is defined; the main factors that are important in preparing high school students for choosing a direction of professional activity.
Keywords: PROFESSIONAL SELF-DETERMINATION OF HIGH SCHOOL STUDENTS